2019
DOI: 10.1111/jar.12681
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of meaningful occupation: Employment and occupational outcomes for older Irish adults with an intellectual disability

Abstract: Background Adults with an intellectual disability (ID) have much lower rates of employment than their counterparts without intellectual disability, which increases their risk of poverty and social exclusion. Differential treatment of people with intellectual disability in welfare and training policies suggests an expectation they will be passive welfare recipients rather than productive employees. Methods This paper aims to examine occupational activities by older people with intellectual disability in Ireland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Meaningful activities positively impact health, quality of life (QOL), and well‐being (Fleming et al, 2013; Heggebø, 2016; McCausland et al, 2020; van der Noordt et al, 2014). Schalock's (2002) model of QOL includes perceptions, behaviours, and conditions that reflect a person's well‐being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meaningful activities positively impact health, quality of life (QOL), and well‐being (Fleming et al, 2013; Heggebø, 2016; McCausland et al, 2020; van der Noordt et al, 2014). Schalock's (2002) model of QOL includes perceptions, behaviours, and conditions that reflect a person's well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that a higher level of functioning increases the likelihood of employment (Martorell et al, 2008;McCausland et al, 2020) and that the ability to manage activities of daily living is the best predictor of success in work for this population (Eagar et al, 2006;McCausland et al, 2020).…”
mentioning
confidence: 99%
“…Therefore, working enables the individuals to improve their productivity and gain the employee role (Kielhofner, 2002; Kielhofner & Barrett, 1998). Employment is when individuals receive financial benefits from the work they have been doing (Kielhofner, 2009; McCausland et al, 2020). Employment enables individuals to acquire financial independence through the work they are doing, meet societal expectations, experience success and obtain self‐management skills (Gobelet & Franchignoni, 2006; Ross, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors affecting the employment rates of individuals with intellectual disability including the environmental, cultural, economic and political factors as well as the abovementioned individual factors (Channon, 2014). However, according to McCausland et al while most individuals with intellectual disabilities do not engage in employment, most of them engage in some other form of occupation, or another occupational activity such as sports activities, handcrafting activities and music (Abdülbaki et al, 2017; Hekim & Tokgöz, 2016; McCausland et al, 2020). Additionally, in most cases, individuals with intellectual disabilities find these occupational activities meaningful and value these activities greatly (McCausland et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation